Production and characterization of thermostable lipase from locally isolated yeast - Zulkifli, Nurul Izzati (2015)
Demanding of thermostable lipase has increased for industrial processes where normally high reaction temperatures were used. Pichia guilliermondii strain RT (isolate RT) was previously isolated from rotten tomato at night market, Sri Serdang, Selangor. This newly isolated yeast was reported to produce an intracellular thermostable lipase. Previously, isolate RT produced low lipase activity and the characteristics of the thermostable lipase in this wild type yeast were still unknown. Therefore, finding of new lipase producers followed by optimization in order to improve and increase the efficiency of lipase production without increasing cost are very important. This study was concerned to optimize the physical factors for maximum lipase production and characterize the crude enzyme activity of the locally isolated yeast. For determining lipase activity, yeast was qualitatively screened on Rhodamine B-olive agar plate. Optimization of physical factors for maximum lipase production incorporated three different parameters: agitation rates, incubation temperature and incubation time. Then, characterization of optimum temperature and pH were evaluated to determine crude enzyme activity. This study revealed isolate RT showed maximum lipase yield at 200 rpm with incubation at 30 °C for 72 hours. The optimum temperature was at 75 °C and can retain nearly 50 % of initial activity after preincubated for 30 minutes at 75 °C. In addition, isolate RT was found to be optimum in alkaline condition at pH 9. This study indicated that favourable growth parameters and characterization of crude enzyme in wild type yeast were significant and played key roles in maximum lipase production and activity.